Minimally invasive triple valve surgery: A single center experience. Issue 10 (15th July 2020) - Moront, Michael G.; Kuehne, Michael; Redfern, Roberta E.
Abstract: Objective: Minimally invasive surgery is a widely accepted surgical treatment for valve disease, however triple valve surgery (TVS) is a complex and challenging procedure. The objective of this study was to describe the morbidity and mortality related to minimally invasive TVS at our institution. Methods: This was a retrospective review of all minimally invasive TVS performed between 2012 and 2019. Baseline and perioperative characteristics were reviewed, as were postoperative outcomes. Results: Eighteen patients underwent TVS; 12 patients underwent additional procedures at the time of TVS. Median time to initial extubation was 11.5 hours (interquartile range [IQR] 9.8‐13.3). Intensive care unit and total length of stay were 1.22 (IQR, 1.16‐1.31) and 9 (IQR, 6‐17) days, respectively. No hospital deaths occurred; 30‐, 90‐, and 365‐day mortality were 0%. Two postoperative neurologic complications occurred, two patients had acute kidney injuries. The most common complication was rhythm disturbance with five patients requiring permanent pacemaker implantation. Mean follow‐up was 39.9 months (252‐2642 days). Conclusions: Our findings demonstrate that minimally invasive TVS utilizing femoral cannulation results in an acceptable risk of complication. Short and intermediate term survival were excellent.